Reflection on Assessing the Development of Children after Epilepsy Surgery - van Schooneveld, Monique; Jennekens-Schinkel, Aag (Journal of Pediatric Epilepsy, 2018)
Children of schoolage having similar medical and neuropsychological conditions but entirely different life courses after left-sided hemispherectomy led us to reflect on sources of differences in development after epilepsy surgery. Two recent reviews exposed the impact of epilepsy-related variables on the cognitive outcomes and concluded that overall the surgical procedures had not caused additional harm. Our aim was to see whether facilitating or impeding influences—other than epilepsy and epilepsy surgery—were addressed in the literature regarding cognitive outcome. Further review of the literature did not yield information on influences of variables that are known to affect normal development; no study addressed influences of motor and/or sensory impairments. Few studies discussed interference of deficits in other cognitive domains with the target domains. The influences of gender and of an important environmental aspect, family factors, etc., were underexposed as well. Understanding why one child adjusts to her/his novel life situation and another child with apparently similar abilities and impairments is unable to do so, is essential for adequate counseling. A more biographical approach of cognitive development is proposed to understand the differential life courses of children and adolescents with a history of epilepsy surgery. A perspective of “functioning” rather than cognitive “functions,” conceived of as independent entities, will help bridge the gap between neurocognitive and more biographical approaches to the functioning of children after epilepsy surgery.
Keywords: children; cognitive outcome; development; epilepsy surgery